Analisis Faktor-Faktor Kesulitan Belajar Pelajaran Al-Islam Di SMP Muhammadiyah 1 Metro - Latri Ida Aini; apip, Afifuddin Ahmad Robbani (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2023)
Learning difficulties are defined as conditions in the learning process which are characterized by the existence of certain obstacles in achieving learning outcomes. In the Al-Islam subject, especially in Al-Qur'an Hadith material, there are students who find it difficult to memorize the Al-Qur'an and Hadith. This shows that students have learning difficulties. Therefore it is necessary to carry out research to find out the factors that cause students' difficulties in memorizing the Al-Qur'an and Hadith. This research is a descriptive qualitative research, with primary data namely students and teachers of Al-Islam subjects. Secondary data sources, such as school documents and archives. This study uses data collection techniques, namely interviews and documentation. The guarantor of the validity of the data used is technical triangulation. The data analysis techniques are data reduction, data presentation, and drawing conclusions. Based on the results of research on students' difficulties in memorizing the Al-Qur'an and Hadith, it is known that the students' interest in memorizing is low, the ability to read the Al-Qur'an is low, they feel bored, and the verses and hadiths that are memorized are too long. Then the lack of parental involvement in their children's learning process, the many assignments given by the teacher make it difficult for students to divide their time to do assignments and memorize the Al-Qur'an and Hadith. The efforts made in overcoming the difficulties of memorizing students by trying to repeat each verse and hadith that are being memorized, following the BTQ subject, then the efforts of the Al-Islam subject teacher invite students to read the verses and hadiths that will be memorized in advance. together, writing verses and hadiths in Latin letters to make it easier for students who cannot read the Qur'an fluently, outdoor learning to reduce student boredom, and providing motivation.